Pendampingan Konstruksi dan Analisis Asesmen Diagnostik dalam Implementasi Kurikulum Merdeka di SMPN 1 Mempura Siak: Construction Mentoring and Diagnostic Assessment Analysis in Implementing the Independent Curriculum at SMPN 1 Mempura Siak - Suryawati, Evi; Natalina, Mariani; Sayuti, Irda; Darmadi, Darmadi; Dianti, Putri Rahma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Learning assessment in the Independent Curriculum aims to provide an overview of student learning progress in cognitive, skill, and attitudinal areas. Diagnostic assessment is a preliminary step that must be conducted before teachers design learning activities. Problem identification in the field indicates that teachers at SMPN 1 Mempura face challenges in developing quality diagnostic assessments tested for validity and reliability. Therefore, SMPN 1 Mempura requires assistance and training in implementing the Independent Curriculum, specifically in the design, implementation, and evaluation of diagnostic assessments. The service activities were conducted over six meetings, totaling 32 learning hours. These activities followed structured steps: preparation, implementation, evaluation, and measuring success through indicators. This training was deemed successful in enhancing teachers' understanding and practical skills in compiling and analyzing diagnostic assessments, which are crucial for implementing the Independent Curriculum effectively.